Efeito hipolipidêmico e hepatoprotetor do 4,4’-dicloro-difenil disseleneto em um modelo de hiperlipidemia em ratos - Heck, Suélen Osório (2016)
Hyperlipidemia can be manifested by elevation in total cholesterol (TC), triglycerides (TGs) and low density lipoprotein (LDL), as well as by reduction in high density lipoprotein (HDL) levels. Hyperlipidemia is associated with oxidative stress and endothelial damage followed by atheroma and cardiovascular disease (CVDs) development. Moreover, high lipid levels are related with non alcoholic fatty liver disease (NAFLD). In view of the limitations and side effects of current drugs to treat hyperlipidemia, it becomes interesting to search for new drugs with hypolipidemic and hepatoprotective effects. The purpose of this study was to investigate the possible hepatoprotective and antihyperlipidemic effects of 4,4'-dichlorodiphenyl diselenide [(p-ClPhSe)2] in a hyperlipidemia model induced by Triton WR-1339 in rats. Biochemical analyses and hepatic oxidative stress parameters were evaluated in rats exposed to triton WR-1339 (400 mg/kg; i.p.) and treated with (p-ClPhSe)2 (10 mg/kg; i.g.) for seven days. After triton WR-1339 injection and fasting for 18 hours, the animals were exposed to the activity monitor for evaluation of exploratory and locomotor activity. Subsequently, blood was collected for determining biochemical parameters. The levels of TC, TGs, non-HDL-cholesterol (non-HDL), coronary risk index (CRI), reactive oxygen species, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities were significantly increased in triton treated rats. (p-ClPhSe)2 treatment resulted in a significant decrease in plasma lipid levels and was effective in normalizing the enzyme activities. (p-ClPhSe)2 did not protect against the increase of ROS levels, but increased NPHS levels in triton treated animals. (p-ClPhSe)2 could have potential in hyperlipidemia treatment as well as to reduce liver damage caused by this disorder.